2003
DOI: 10.1038/sj.npp.1300217
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Interleukin-6 in the Cerebrospinal Fluid of a Previously Delineated Schizophrenia Subtype

Abstract: Evidence of immune activation has occasionally, but not consistently, been reported in schizophrenia. Investigations of cytokine abnormalities in serum, and occasionally in CSF, have yielded inconsistent results, which have been difficult to resolve. In such studies, schizophrenia has been assumed to consist of a single process rather than a group of disorders. This study assesses differences in the proinflammatory cytokine, interleukin-6 (IL-6) in the cerebrospinal fluid (CSF) in two previously delineated sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(73 citation statements)
references
References 36 publications
1
69
0
Order By: Relevance
“…Similar increases in inflammatory cytokines and acute-phase reactants have also been reported in patients with bipolar disorder and schizophrenia, including meta-analyses (Goldsmith et al, 2016b;Miller et al, 2011;Potvin et al, 2008). Increased inflammatory cytokine concentrations in the cerebrospinal fluid (CSF) of patients with unipolar and bipolar depression, and schizophrenia have also been observed (Garver et al, 2003;Levine et al, 1999;Schwieler et al, 2015;Soderlund et al, 2011;Soderlund et al, 2009). In MDD, CSF cytokines have been shown to be associated with the severity of depression or with the change in symptoms in response to successful treatment (Levine et al, 1999;Lindqvist et al, 2009;Martinez et al, 2012).…”
Section: Increased Inflammation In Psychiatric Disordersmentioning
confidence: 66%
See 1 more Smart Citation
“…Similar increases in inflammatory cytokines and acute-phase reactants have also been reported in patients with bipolar disorder and schizophrenia, including meta-analyses (Goldsmith et al, 2016b;Miller et al, 2011;Potvin et al, 2008). Increased inflammatory cytokine concentrations in the cerebrospinal fluid (CSF) of patients with unipolar and bipolar depression, and schizophrenia have also been observed (Garver et al, 2003;Levine et al, 1999;Schwieler et al, 2015;Soderlund et al, 2011;Soderlund et al, 2009). In MDD, CSF cytokines have been shown to be associated with the severity of depression or with the change in symptoms in response to successful treatment (Levine et al, 1999;Lindqvist et al, 2009;Martinez et al, 2012).…”
Section: Increased Inflammation In Psychiatric Disordersmentioning
confidence: 66%
“…In MDD, CSF cytokines have been shown to be associated with the severity of depression or with the change in symptoms in response to successful treatment (Levine et al, 1999;Lindqvist et al, 2009;Martinez et al, 2012). In schizophrenia, increased cytokines have been associated with delayed treatment response (Garver et al, 2003), and in bipolar disorder, they are higher in patients that have had more recent manic or hypomanic episodes (Soderlund et al, 2011).…”
Section: Increased Inflammation In Psychiatric Disordersmentioning
confidence: 99%
“…A combination of genetic and environmental factors resulting in some immune dysregulation in general and the lack of the CMV IgG antibodies in particular could be the most plausible speculations. While there are no specific research results supporting this finding in existing literature, the activation of the immune system and prolonged neuroinflammation are well established phenomena implicated in the etiopathogenesis and symptomatology of schizophrenia (Lin et al, 1998;Nikkila et al, 1999;Kim et al, 2000;Theodoropoulou et al, 2001;Ebrinc et al, 2002;Patterson, 2002;Zhang et al, 2002;Garver et al, 2003;Zhang et al, 2004;Coelho et al, 2008;Potvin et al, 2008;Doorduin et al, 2009;Kim et al, 2009;Song et al, 2009;Drexhage et al, 2010;Romero et al, 2010;Drexhage et al, 2011;Weigelt et al, 2011;Beumer et al, 2012;Brito-Melo et al, 2012). Other mechanisms could also be considered.…”
Section: Discussionmentioning
confidence: 83%
“…13 A few studies have also shown that CSF IL 6 is elevated in patients with chronic schizophrenia. 14,15 Al though evidence of immune activation in schizophrenia is emerging, its functional relationship to aberrant brain neuro transmission and behaviour has been unclear. Activation of the kynurenine (KYN) pathway has been suggested as a mech anism serving to transfer information from the immune sys tem of the brain to neurons.…”
Section: Introductionmentioning
confidence: 99%